Advances in Fluid Mechanics X 2014
DOI: 10.2495/afm140181
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of the deformation of charged drops of electrolyte

Abstract: The volume-of-fluid based numerical method of Berry et al. (J. Computational Physics, 251, pp. 209-222, 2013), for predicting electrokinetic flow of multiphase flow with deformable interfaces, is extended to account for the effect of interfacial charge. The numerical representation of interfacial charge is validated using two simple test cases. Finally, the use of the extended algorithm is demonstrated by simulating the breakup of an unstable charged water drop in air.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Their results include computations of tip streaming drops. Related numerical work includes [43][44][45]. A strong motivation for theoretical and numerical analysis of the electrokinetic models is their significance in microfluidic devices, for which electrokinetic techniques have been among the most important methods for the manipulation of drops and bubbles [46].…”
Section: Introductionmentioning
confidence: 99%
“…Their results include computations of tip streaming drops. Related numerical work includes [43][44][45]. A strong motivation for theoretical and numerical analysis of the electrokinetic models is their significance in microfluidic devices, for which electrokinetic techniques have been among the most important methods for the manipulation of drops and bubbles [46].…”
Section: Introductionmentioning
confidence: 99%
“…9To account for interfacial charges, two methods were evaluated elsewhere (Davidson et al, 2014), which are the delta function formulation and another one adapted from (Liu et al, 2000) that accounts for jump in electric displacement due to interfacial charges and discontinuity in permittivity across interface. Davidson and co-workers (Davidson et al, 2014) concluded that the second one was more satisfactory to represent the electrical potential jump in the interface. Explicit expressions and formulations for the method can be found in (Davidson et al, 2014, Liu et al, 2000.…”
Section: Governing Equations and Dimensionless Groupsmentioning
confidence: 99%
“…Davidson and co-workers (Davidson et al, 2014) concluded that the second one was more satisfactory to represent the electrical potential jump in the interface. Explicit expressions and formulations for the method can be found in (Davidson et al, 2014, Liu et al, 2000.…”
Section: Governing Equations and Dimensionless Groupsmentioning
confidence: 99%
See 2 more Smart Citations